Literature Review of the Effectiveness of Using Aggregate Planing in the Msme Industry - Cahyono, Antonius; Prihono, Prihono; Febrianto, Indra Dwi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This research investigates the effectiveness of using Aggregate Planning in the Micro, Small and Medium Enterprises (MSME) industry. Through a literature review using national and international scientific journal articles from 2018-2023, this research identified three main approaches to aggregate planning: Level Strategy, Chase Strategy, and Mixed Strategy. Level Strategy maintains production levels at a constant level, using inventory as a buffer to deal with fluctuations in demand. Chase Strategy adjusts production directly to market demand, minimizing inventory and carrying costs. Mixed Strategy, a combination of Chase Strategy and Level Strategy, combines the flexibility of Chase Strategy with the stability of Level Strategy to optimize production and inventory costs. This research describes how MSMEs in the children’s clothing industry implement these three strategies. In Level Strategy, production is kept at a constant level, using inventory as a buffer. In the Chase Strategy, production is matched directly to demand, reducing inventory and carrying costs. In Mixed Strategy, the combination of strategies allows flexible response to demand fluctuations, minimizing inventory costs. The calculation results show that using Mixed Strategy allows companies to optimize production, reduce inventory costs, and respond quickly to variations in market demand. The total costs during this period were the result of production costs, inventory costs, overtime costs, and worker salaries, reaching a total of IDR 124,900,000. This research provides insight into how MSMEs can utilize aggregate planning with various strategies to increase their operational efficiency and flexibility in facing market dynamics.